2013
DOI: 10.1155/2013/827674
|View full text |Cite
|
Sign up to set email alerts
|

Heath Beliefs of UK South Asians Related to Lifestyle Diseases: A Review of Qualitative Literature

Abstract: Objective. To review available qualitative evidence in the literature for health beliefs and perceptions specific to UK South Asian adults. Exploring available insight into the social and cultural constructs underlying perceptions related to health behaviours and lifestyle-related disease. Methods. A search of central databases and ethnic minority research groups was augmented by hand-searching of reference lists. For included studies, quality was assessed using a predetermined checklist followed by metaethnog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 22 publications
(102 reference statements)
3
74
2
Order By: Relevance
“…The dietary education implied a change of cooking methods, but some participants found that this change of cooking methods was not possible if they wanted the food to taste good and look good. Specific preferences for cooking methods and taste as well as the perception of traditional food as unhealthy have been addressed in other studies 20,21,23. As in our study, Fagerli et al also found that Pakistani participants struggled with translating dietary advice and applying it to their own life because of health workers’ lack of knowledge about cross-cultural variations in dietary practices 20.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The dietary education implied a change of cooking methods, but some participants found that this change of cooking methods was not possible if they wanted the food to taste good and look good. Specific preferences for cooking methods and taste as well as the perception of traditional food as unhealthy have been addressed in other studies 20,21,23. As in our study, Fagerli et al also found that Pakistani participants struggled with translating dietary advice and applying it to their own life because of health workers’ lack of knowledge about cross-cultural variations in dietary practices 20.…”
Section: Discussionsupporting
confidence: 62%
“…In a review concerning health beliefs of South Asians residing in the UK, consumption of food was found to play an important role in social networks, in the creation of social networks by giving gifts of luxurious or traditional foods, and through the social significance of cooking for guests and of eating celebratory meals 21. Participants in our study also mentioned food challenges with regard to social practices and events, such as visiting relatives in Pakistan and celebrations during Ramadan and weddings, but participants did not discuss these issues with health care professionals in the educational setting.…”
Section: Discussionmentioning
confidence: 99%
“…The study presented a unique exploratory insight into the phenomena of enhancement drug use among acculturated British South Asian males. Absence of exercise culture and lack of physical activity among British South Asian groups have traditionally been observed (Duncan, Woodfield, Al-Nakeeb, & Nevill, 2008;Lucas, Murray, & Kinra, 2013;Williams, Stamatakis, Chandola, & Hamer, 2011). British South Asian male bodies are also not well represented in British sport, fitness and leisure media (Brettingham, 2007;Farooq & Parker, 2009;Malcolm, Bairner, & Curry, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Adherence with treatment could be reduced in Aboriginal patients, perhaps reflecting ethnicity-specific differences in disposable income, prioritisation of health behaviours and the understanding of treatment benefits that can occur in disenfranchised minorities [32,33]. However, the potentially serious consequences of untreated depression, including in the specific context of diabetes [4][5][6][7], highlight the need for greater awareness of this diagnosis in the management of indigenous patients.…”
Section: Discussionmentioning
confidence: 99%